Uterine Natural Killer Cells: Functional Distinctions and Influence on Pregnancy in Humans and Mice - Gaynor, Louise M.; Colucci, Francesco (Frontiers in Immunology, 2017)
Our understanding of development and function of Natural Killer (NK) cells has progressed significantly in recent years. However, exactly how uterine NK (uNK) cells develop and function is still unclear. To help investigators that are beginning to study tissue NK cells, we summarize in this review our current knowledge of the development and function of uNK cells, and what is yet to be elucidated. We compare and contrast the biology of human and mouse uNK cells in the broader context of the biology of innate lymphoid cells and with reference to peripheral NK cells. We also review how uNK cells may regulate trophoblast invasion and uterine spiral arterial remodeling in human and murine pregnancy.